INTEGRATION OF EDUCATION AND TRAINING IS A FACTOR OF ACHIEVING THE GOAL (American Journal of Interdisciplinary Research and Development, 2022)
The article talks about the integrality of education and training factors in the development of the young generation into a perfect person. In this, issues such as the family environment, the role of the community - the neighborhood will be covered, and attention will be paid to the problems related to preparing children for school.